ANALYSIS OF THE EFFECT OF ELECTRONIC WORD OF MOUTH, BRAND IMAGE AND TRUST ON PATIENTS' REVISIT INTENTION IN DENTAL AND MOUTH HOSPITAL ANDALAS UNIVERSITY - Berlian Kurnia Wati; Hardisman Hardisman; Verinita Verinita (JURNAL ECONOMICA : Research of Economic And Economic Education, 2025)
This study aims to prove and analyze the influence of electronic word of mouth, brand image and trust on patient revisit interest at the Dental and Oral Hospital of Andalas University. This study used 120 patients who had at least one experience of visiting and using the services of the Dental and Oral Hospital (RSGM) at Andalas University in the past year. The sample collection method used was purposive sampling. Data collection was carried out by survey through the distribution of questionnaires. The distribution process was carried out via a google form link. The data analysis method used to prove the truth of the hypothesis was multiple linear regression (OLS) while hypothesis testing was carried out using the t-statistic test. In accordance with the results of the first hypothesis test, it was found that electronic word of mouth did not have a significant effect on patient revisit interest at RSGM Unand Padang. In the second and third stages of hypothesis testing, it was found that brand image and trust each had a positive and significant effect on patient revisit interest at RSGM Unand Padang